The Ever-Changing and Challenging Role of Ocean Observation: From Local Initiatives to an Oceanwide Collaborative Effort - Silveira, Tanya Mendes; Carapuço, Mafalda Marques; Miranda, Jorge Miguel (Frontiers in Marine Science, 2022)
Ocean observation has seen a rapid evolution and has become crucial in providing the much needed data and information toward a well-supported and accurate description of ocean processes which influence the environmental, economic, and societal systems. There has been a significant progress in technologies which have enabled the expansion of the sampling and observing systems both on temporal and spatial scales. Furthermore, online, free access, data portals have grown in number and quality, provided by data aggregators, which have promoted the creation of standardized methods for marine data acquisition and management. Ocean observation is now global, but it depends on the single institutions and laboratories’ capability to guarantee the operation of instruments and longevity in data acquisition. International collaborative initiatives are crucial to support the ever-growing databases and feed the services and products that are fundamental to Blue Growth. Collaboration must be developed at local and regional levels and the monitoring system must ensure data consistency, integrity, and redundancy. The “Atlantic Observatory – Data and Monitoring Infrastructure” project, is an example of a Portuguese effort to bring together on-going initiatives working in the Atlantic area and provide access to high quality marine environmental data covering the Atlantic Ocean basin.